Comparison of thoracoabdominal versus abdominal-transhiatal surgical approaches in Siewert type II adenocarcinoma at the esophagogastric junction: Protocol for a prospective multicenter randomized controlled trial - Yue, Chao; Mo, Zhenchang; Wu, Xiao; Wang, Yannian; Yang, Qinchuan; Wang, Weidong; Zhou, Haikun; Gao, Ruiqi; Ji, Panpan; Dong, Danhong; Zhang, Ying; Ji, Gang; et al. (Frontiers in Oncology, 2023)
Background: Siewert type II adenocarcinoma of the esophagogastric junction (Siewert II AEG) can be resected by the right thoracoabdominal surgical approach (RTA) or abdominal-transhiatal surgical approach (TH) under minimally invasive conditions. Although both surgical methods achieve complete tumor resection, there is a debate as to whether the former method is superior to or at least noninferior to the latter in terms of surgical safety. Currently, a small number of retrospective studies have compared the two surgical approaches, with inconclusive results. As such, a prospective multicenter randomized controlled trial is necessary to validate the value of RTA (Ivor-Lewis) compared to TH. Methods: The planned study is a prospective, multicenter, randomized clinical trial. Patients (n=212) with Siewert II AEG that could be resected by either of the above two surgical approaches will be included in this trial and randomized to the RTA group (n=106) or the TH group (n=106). The primary outcome will be 3-year disease-free survival (DFS). The secondary outcomes will include 5-year overall survival (OS), incidence of postoperative complications, postoperative mortality, local recurrence rate, number and location of removed lymph nodes, quality of life (QOL), surgical Apgar score, and duration of the operation. Follow-ups are scheduled every three months for the first 3 years after the surgery and every six months for the next 2 years. Discussion: Among Siewert II AEG patients with resectable tumors, this is the first prospective, randomized clinical trial comparing the surgical safety of minimally invasive RTA and TH. RTA is hypothesized to provide better digestive tract reconstruction and dissection of mediastinal lymph nodes while maintaining a high quality of life and good postoperative outcome. Moreover, this trial will provide a high level of evidence for the choice of surgical procedures for Siewert II AEG.